Prokaryotic Expression of Recombinant Fusion Gene CAT-SYI from Streptococcus Mutans - Feng, Pan; Li, Zaixin (International Journal of Public Health and Medical Research, 2026)
Objective: To express and purify the recombinant fusion protein CAT SYI of Streptococcus mutans, and to provide basic materials for subsequent immunogenicity research and the development of anti caries vaccines. Methods: The recombinant plasmid pET32a CAT SYI constructed previously in our laboratory was transformed into Escherichia coli DH5α for amplification. After PCR verification, the correctly identified plasmid was transformed into the expression strain BL21. The expression of the recombinant fusion protein was induced by IPTG, and the induction conditions including IPTG concentration (0.25-1.5mM), induction time (0-10h) and induction temperature (26℃,37℃) were optimized. The bacterial cells were disrupted by ultrasonication, and the recombinant protein was purified and refolded by urea gradient dialysis. The expression and purification efficiency were analyzed by SDS PAGE. Results: PCR identification confirmed that the recombinant plasmid pET32a CAT SYI was successfully constructed, with an amplified fragment of approximately 750bp. SDS PAGE analysis showed that the recombinant fusion protein was successfully expressed with a molecular weight of about 50kDa, which was consistent with the expected value. The optimal induction conditions were determined as follows: final IPTG concentration of 1.25mM, induction time of 6 h, and induction temperature of 37℃. Soluble target protein was obtained after dialysis and refolding of the purified recombinant protein. Conclusion: The high efficiency expression of the recombinant fusion protein CAT SYI from Streptococcus mutans in Escherichia coli was successfully achieved, and the corresponding induction optimization and purification methods were established. These results lay an experimental foundation for the subsequent evaluation of immune protective efficacy and the research and development of anti caries vaccines.